Nutrition Journal - Collins, Clare; Kirkpatrick, Sharon; Kerr, Deborah; Keogh, Ruth; Burrows, Tracy; Robinson, Sian
Nutrition Journal publishes novel surveillance, epidemiologic, and intervention research that sheds light on i) influences (e.g., familial, environmental) on eating patterns; ii) associations between eating patterns and health, and iii) strategies to improve eating patterns among populations. The journal also welcomes manuscripts reporting on the psychometric properties (e.g., validity, reliability) and feasibility of methods (e.g., for assessing dietary intake) for human nutrition research. In addition, study protocols for controlled trials and cohort studies, with an emphasis on methods for assessing dietary exposures and outcomes as well as intervention components, will be considered. Manuscripts that consider eating patterns holistically, as opposed to solely reductionist approaches that focus on specific dietary components in isolation, are encouraged. Also encouraged are papers that take a holistic or systems perspective in attempting to understand possible compensatory and differential effects of nutrition interventions. The journal does not consider animal studies. In addition to the influence of eating patterns for human health, we also invite research providing insights into the environmental sustainability of dietary practices. Again, a holistic perspective is encouraged, for example, through the consideration of how eating patterns might maximize both human and planetary health.